Leptin Promotes Greater Ki67 Expression in CD4+ T Cells From Obese Compared to Lean Persons Living With HIV - Fuseini, Hubaida; Smith, Rita; Nochowicz, Cindy H.; Simmons, Joshua D.; Hannah, LaToya; Wanjalla, Celestine N.; Gabriel, Curtis L.; Mashayekhi, Mona; Bailin, Samuel S.; Castilho, Jessica L.; Hasty, Alyssa H.; Koethe, John R.; et al. (Frontiers in Immunology, 2022)
While antiretroviral therapy (ART) has proven effective in suppressing viremia and disease progression among people living with human immunodeficiency virus (HIV; PLWH), suboptimal CD4+ T cell reconstitution remains a major obstacle in nearly 30% of ART-treated individuals. Epidemiological studies demonstrate that obesity, or a body mass index (BMI) ≥ 30 kg/m2, is positively correlated with greater CD4+ T cell recovery in PLWH on ART. Leptin is a known immunomodulator that is produced in proportion to fat mass and is increased in obese individuals, including PLWH. We hypothesized that CD4+ T cells from obese PLWH have increased cell proliferation and cytokine production compared to cells from lean PLWH, potentially modulated by differential effects of leptin signaling. To test this hypothesis, peripheral blood mononuclear cells from obese and lean PLWH with long-term virologic suppression on the same ART regimen were pretreated with recombinant leptin and then stimulated with anti-CD3/CD28 or PMA/ionomycin to measure Ki67 expression, leptin receptor (LepR) surface expression and cytokine production. In the absence of leptin, Ki67 expression and IL-17A production were significantly higher in CD4+ T cells from obese compared to lean PLWH. However, LepR expression was significantly lower on CD4+ T cells from obese compared to lean PLWH. After leptin treatment, Ki67 expression was significantly increased in CD4+ T cells from obese PLWH compared to the lean participants. Leptin also increased IL-17A production in CD4+ T cells from obese healthy controls. In contrast, leptin decreased IL-17A production in CD4+ T cells from both obese and lean PLWH. Combined, these results demonstrate that obesity is associated with greater CD4+ T cell proliferation among PLWH, and that higher circulating leptin levels in obesity may contribute to improved CD4+ T reconstitution in PLWH initiating ART.